The role of Artificial Intelligence in Cyber Security and Incident Response: Syed Khurram Hassan, Asif Ibrahim - Syed Khurram Hassan; Asif Ibrahim (International Journal for Electronic Crime Investigation, 2023)
The escalating number and intricacy of cyber attacks have underscored the urgent requirement for innovative solutions to bolster the security of digital infrastructure. Among these solutions, Artificial Intelligence (AI) emerges as a promising technology with the potential to significantly enhance cyber security and incident response. It has the aptitude to improve the speed and accuracy of threat detection, response and mitigation while also reducing the workload on security professionals. This research paper focuses on the role of AI in key areas of cyber security and incident response, specifically vulnerability assessment, intrusion detection and prevention, and digital forensics analysis. It elucidates how AI, with its innate capabilities, can be a game-changer by empowering organizations to detect, respond to, and mitigate threats more effectively. However, AI is not a silver bullet for Cyber Security. Like any technology, it possesses its limitations and potential vulnerabilities. Consequently, this paper also addresses the need for ongoing development in the field of AI to overcome these limitations and challenges. By recognizing the need for continuous advancements, the research paper emphasizes the importance of future research and development efforts to maximize the potential benefits of AI in the realm of cyber security.